Programas internacionais de transição pós-escolar para pessoas com deficiência intelectual desenvolvidos na universidade: uma revisão de escopo - Leite, Graciliana Garcia (Universidade Federal de São Carlos, 2023)
Young people go through the important experience of transitions as they move into independent adulthood. The literature highlights that young people with intellectual disabilities generally perform worse in aspects of adult life, such as education, work, independent living, among others, when compared to a group without disabilities. From this perspective, post-secondary transition programs can help develop skills and abilities to increase the likelihood of success in independent adult life. Considering the Brazilian reality, in which there is a shortage of these programs, it is necessary to better understand the scenario from other perspectives. Therefore, this paper aims to: (a) characterise the international view on post-secondary transition programs, in the university context, for people with intellectual disabilities, taking as its starting point the United Nations Convention on the Rights of Persons with Intellectual Disabilities; (b) identify the skills and areas addressed in these programs and the effects on the lives of people with intellectual disabilities; (c) analyse the implications of these programs on people with intellectual disabilities in the university context, through a scoping review, taking as a reference the period from January 2006 to December 2022. The research included online databases such as Academic Search Premier ASP (EBSCO), Education Resource Information Center (Eric), PsycInfo (APA), CINAHL with Full Text (EBSCO), Web of Science Core Collection (Clarivate Analytics), and Scopus (Elsevier) and gray literature (Google Scholar, Global ETD Search, and DART-Europe E-thesis), as well as consulting the list of references of relevant studies. Data extraction from the studies was carried out by the main author and a reviewer using a previously developed and validated form. The synthesis of the extracted data focused on qualitative analyses, and the results were organised into thematic categories. The search strategy identified a total of 3,253 records, of which 34 searches were selected for inclusion and analysis. The results indicate that the majority of studies were published in the last 7 years (73.5%), in the United States and Spain. Most post-secondary transition programs last two years, predominantly inclusive types ones. The main areas the programs address are employment preparation and career development, academic development, self-determination skills, independent living, and socialising. Students who participated in the programs had higher employability rates, development of independent living skills, increased i and social skills. Post-secondary transition programs play a key role in the transition to independent adulthood for young people with intellectual disabilities. The set of skills taught along with the experience of participating in activities on a university campus with peers without disabilities constitute an opportunity that benefits preparation for independent adult life. Although there were some limitations to the information available in the collected data, this scoping review contributed to characterising post-secondary transition programs that act in the process of transition and preparation for independent adult life for people with intellectual disabilities.
International post-secondary transition programs for people with intellectual disabilities developed in university: scoping review
Keywords: Educação especial; Special education; Post-secondary education programs; Programas de educação pós-secundário; Vida adulta independente; Independent adult life; Transição; Transition; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO